Media Tradisional Aceh Dalam Perspektif Komunikasi Islam - rahmadianawati (Pascasarjana IAIN Lhokseumawe, 2019)
Acehnese people is known as a religious community. Islamic religion plays an important role in directing the behavior of everyday society. This is reflected in the traditional art that developed in the life of the people of Aceh. This paper seeks to examine the elements of Islamic found in traditional media Aceh. In this case a form of dance or art speech because this art is a broadcast media propaganda in Islam of Kesulthanan Ocean Pasai to various regions in the archipelago even to Southeast Asia. This exploratory study used a qualitative approach. The study found that the traditional art of Aceh in line with the rules and guidelines laid down by Islam. Other Islamic spirit reflected in the art of Aceh in the form of the art of motion and sound art is all art is always accompanied with a poem that contains the elements and values of propaganda.